Is the beneficiary pays principle essential in climate justice? - Clare Heyward (Norsk Filosofisk Tidsskrift)
Abstract The United Nations Framework Convention on Climate Change principle of ‘common but differentiated responsibility’ admits many interpretations. In the philosophical literature on climate justice, it has typically been cashed out in terms of the following three principles: the ability to pay principle (APP), the beneficiary pays principle (BPP), and the contribution to problem principle (CPP). Many of these accounts have given prominence to the CPP and APP, but there are some who argue that the BPP deserves greater consideration. In this paper, I want to ask whether the BPP must feature in any plausible account of remedial responsibility for climate change. I examine this question by looking at three different ways in which the BPP has been incorporated into accounts of climate burden-sharing. In each case, there are questions about the particular role that the BPP is assigned and it looks like either the BPP must be given equal prominence to the CPP, or the BPP might be redundant when it comes to specific task of remedying the injustices of climate change. I suggest in the conclusion one possible reason to maintain the BPP.